THE MATHEMATICAL MODELING OF THE PROCESS OF WASHING AERATION ZONE - Biliaev, M. M.; Kalashnikov, I. V. (Science and Transport Progress, 2008)
A numerical model to calculate the process of soil protection from pollution with the use of neutralizator has been proposed. The model is based on the equation of admixture transfer. The results of numerical experiment are presented.